The role of Mannose Binding Lectin in the immune response against Borrelia burgdorferi sensu lato - Coumou, Jeroen; Wagemakers, Alex; Narasimhan, Sukanya; Schuijt, Tim J.; Ersoz, Jasmin I.; Oei, Anneke; de Boer, Onno J.; Roelofs, Joris J. T. H.; Fikrig, Erol; Hovius, Joppe W. (Scientific reports, 2019)
The causative agents of Lyme borreliosis, spirochetes belonging to the Borrelia burgdorferi sensu lato group, have developed several ways to protect themselves against killing by the host complement system. In addition, it has been shown that serum sensitive isolates are (partially) protected by the Ixodes Tick Salivary Lectin Pathway Inhibitor (TSLPI) protein; a salivary gland protein that inhibits the function of Mannose Binding Lectin (MBL). MBL is a C-type lectin that recognizes oligosaccharides on pathogens and activates the complement system via the lectin pathway. MBL deficiency has been linked to a more severe course of several infectious diseases and humans with detectable antibodies against B. burgdorferi are significantly more often MBL deficient compared to humans without antibodies against B. burgdorferi . Here we set out to investigate the role of MBL in the immune response against B. burgdorferi in more detail. We demonstrate that B. burgdorferi N40 needle-infected C57BL/6 MBL deficient mice harbored significantly higher B. burgdorferi numbers in skin tissue during the early course of infection. In line with these findings they also developed higher anti- B. burgdorferi IgG serum antibodies compared to WT controls. In contrast , B. burgdorferi loads in distant tissue such as heart, joints or bladder at later time points were similar for both mouse strains. These in vivo findings were corroborated using a B. burgdorferi N40-infected I. scapularis infestation model. We showed that MBL is capable of binding B. burgdorferi through its carbohydrate recognition domains, but in vitro complement killing assays, peritoneal macrophage and whole blood stimulations, phagocytosis assays and an in vivo migration experiment did not reveal the mechanism by which MBL facilitates early clearance of B. burgdorferi . To conclude, we show a protective role of MBL in the early stages of B. burgdorferi infection, yet the underlying mechanism warrants further investigation.